National responsibility and global justice - Miller, David 1946- (Oxford political theory, 2007)
This book presents a non-cosmopolitan theory of global justice. In contrast to theories that seek to extend principles of social justice, such as equality of opportunity or resources, to the world as a whole, it argues that in a world made up of self-determining national communities, a different conception is needed. The book presents and defends an account of national responsibility which entails that nations may justifiably claim the benefits that their decisions and policies produce, while also being held liable for harms that they inflict on other peoples. Such collective responsibility extends to responsibility for the national past, so the present generation may owe redress to those who have been harmed by the actions of their predecessors. Global justice, therefore, must be understood not in terms of equality, but in terms of a minimum set of basic rights that belong to human beings everywhere. Where these rights are being violated or threatened, remedial responsibility may fall on outsiders. The book considers how this responsibility should be allocated, and how far citizens of democratic societies must limit their pursuit of domestic objectives in order to discharge their global obligations.